Reading Now and Again: Hyperarchivalism and Democracy in Ranjan Ghosh and J. Hillis Miller's Thinking Literature across Continents. Issue 1 (April 2018) - Fest, Bradley J.
Abstract : This review essay approaches Ranjan Ghosh and J. Hillis Miller's Thinking Literature across Continents (2016) from a set of questions about what it means to read in the age of hyperarchival accumulation. Written against the background of events in the United States and elsewhere during the fall of 2017, the essay tracks and assesses Ghosh and Miller's differing methods for approaching literary study in the twenty-first century: undiscriminating catholicity and rhetorical reading, respectively. Through emblematic readings of David Foster Wallace's novel The Pale King (2011 ), the videogame Katamari Damacy (2004 ), and Amy Hungerford's Making Literature Now (2016 ), this essay argues that Thinking Literature across Continents self-reflexively models and performs the interested, situated reading practices necessary for continuing the never-ending project of encountering, sharing, accounting for, learning from, and contending with others and their divergent readings, practices that, though many may have lost sight of them today, are fundamental to the project of democracy itself.